Silica‐Free Synthesis of Mesoporous Co3O4/CoOxPy as a Highly Active Oxygen Evolution Reaction Catalyst. Issue 11 (30th August 2019) - Sun, Tian; Liu, Piao; Yang, Daihui; Wang, Qiyou; Duan, Junfei; Ma, Chao; Gao, Yang; Zhang, Shiguo
Abstract: Highly active and stable catalysts towards electrochemical oxygen evolution reaction are crucial for the efficient water splitting and sustainable hydrogen generation. Here we report a novel mesoporous Co3 O4 with the surface decoration of mixed CoOx Py species towards efficient OER catalysis. The material is synthesized from a simple carbon template derived from p‐phenylenediamine bisulfate followed by low temperature phosphorization. Unlike traditional methods, silica intermediates are not involved during synthesis, improving the overall safety and efficiency. The as‐prepared mesoporous Co3 O4 /CoOx Py catalyst shows excellent catalytic activity and stability towards oxygen evolution reaction in 1 M KOH. The overpotential is 295 mV at 10 mA cm −2, superior to that of commercial IrO2 /C catalyst. A small Tafel slope of 70 mV dec −1 and high stability are also observed. The excellent electrochemical performance is attributed to the mesoporous structure, strong electronic interaction, and synergistic effect of the mesoporous Co3 O4 and CoOx Py phases. Other heterogeneous catalysts with similar structures and compositions may also be fabricated following the same design principle. Abstract : A simple method of enhancement : A mesoporous Co3 O4 /CoOx Py catalyst was synthesized using a simple silica‐free carbon‐template‐mediated method, and exhibited excellent electrochemical catalytic performance towards oxygen evolution reaction.